Pengunaan Trichoderma sp Pada Poliembrioni Benih Jeruk Siam Madu (Citrus nobillis L) - Habel, Milka Alvionita; Wanget, Sesilia A.; Sumayku, Betrje R.A. (Sam Ratulangi University, 2024)
This study aims to determine the effect of using Trichoderma sp on polyembryony of honey Siamese orange seeds. This research was conducted at the Plant and Environment Laboratory, Sub-Laboratory of Genetics and Plant Breeding, Faculty of Agriculture, Sam Ratulangi University, Manado. The design of this study used a completely randomized design (CRD) with 2 factors, namely the concentration of trichoderma sp. T1 (109), T2 (108), T3 (107) and immersion time, W1 (24 hours), W2 (16 hours), W3 (8 hours). The variables observed were: Germination Power (Viability), Polyembryony, Root Weight. The results of the research showed that Trichoderma sp at a dose of 108 and a soaking time of 8 hours obtained the highest germination of Siam Honey orange seeds. From the results of the polyembryony research on honey Siamese orange seeds using Trichoderma sp, 40% polyembryony was obtained, whereas polyembryonic growth on honey Siamese orange seeds without Trichoderma sp obtained 16,6% polyembryony.